Posted by **Anonymous** on Tuesday, April 24, 2007 at 11:21pm.

2 (x-3)-3(x+5) = 3(x-2) -7

distributive property

2x -6 -3x -15 = 3x -6 -7

combine like terms

-x -21 = 3x -13

add x and 13 to both sides

-7 = 4x

multiply both sides by 1/4

-7/4 = x

## Answer this Question

## Related Questions

- Maths - you have to solve the following by finding the value of x and y. can u ...
- Geometry - Given: 7x + 2 = 2 + 5x – 6 Prove: x = –3 Given the equation 7x + 2...
- Algebra - Can someone please help me with these algebra problems? The directions...
- Distributive property - How would I multiply these expression? 6(h-4) -3(x+8) -...
- algebra--distributive - how would you do this prob. negative4-(5y+6) = negative ...
- Algerbra 1 - 1/3x + 5/6 = 2/9x - 1/3 How do I solve this to get the answer? For ...
- Variable - SOLVING EQUATIONS WITH THE VARIABLE ON BOTH SIDES Solve the equation...
- math - 3(4u-6)=2(4u-3)-(u-8) what is u 12u-18=8u-6-u+8 Can you take it from here...
- Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...
- Distributive Property Algebra - I have two questions I don't understand and I ...